The length of FOXE1 polyalanine tract in congenital hypothyroidism: Evidence for a pathogenic role from familial, molecular and cohort studies - Grassi, Elisa Stellaria; Rurale, Giuditta; de Filippis, Tiziana; Gentilini, Davide; Carbone, Erika; Coscia, Francesca; Uraghi, Sarah; Bullock, Martyn; Clifton-Bligh, Roderick J.; Gupta, Abhinav K.; Persani, Luca (Frontiers in Endocrinology, 2023)
Introduction FOXE1 is required for thyroid function and its homozygous mutations cause a rare syndromic form of congenital hypothyroidism (CH). FOXE1 has a polymorphic polyalanine tract whose involvement in thyroid pathology is controversial. Starting from genetic studies in a CH family, we explored the functional role and involvement of FOXE1 variations in a large CH population. Methods We applied NGS screening to a large CH family and a cohort of 1752 individuals and validated these results by in silico modeling and in vitro experiments. Results A new heterozygous FOXE1 variant segregated with 14-Alanine tract homozygosity in 5 CH siblings with athyreosis. The p.L107V variant demonstrated to significantly reduce the FOXE1 transcriptional activity. The 14-Alanine-FOXE1 displayed altered subcellular localization and significantly impaired synergy with other transcription factors, when compared with the more common 16-Alanine-FOXE1. The CH group with thyroid dysgenesis was largely and significantly enriched with the 14-Alanine-FOXE1 homozygosity. Discussion We provide new evidence that disentangle the pathophysiological role of FOXE1 polyalanine tract, thereby significantly broadening the perspective on the role of FOXE1 in the complex pathogenesis of CH. FOXE1 should be therefore added to the group of polyalanine disease-associated transcription factors.